Strategies for Increasing the Competitiveness of Small and Medium Businesses in the Digital Economy (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes effective strategies for increasing the competitiveness of small and medium-sized businesses in the digital economy. At a time when the economy is transitioning to a digital basis on a global scale, the use of innovative technologies, e-commerce, digital marketing and automated management systems is becoming an important factor for small and medium-sized businesses. The study examines the opportunities for small and medium-sized businesses to reduce costs, expand their customer base, and improve the quality of products and services through modern technologies. The importance of digital infrastructure, state support and digital literacy is also highlighted. Using the example of Uzbekistan, strategies are developed to strengthen the competitiveness of regional small and medium-sized businesses in national and international markets through digital transformation.